PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA INDUSTRI PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - 25, arida (Jurnal KIAFE, 2022)
This study describes the relationship between good corporate governance and financial performance in banking companies. The indicators used to explain corporate governance in this study consist of the size of the board of commissioners, the size of the board of directors and the size of the company. The analytical method used in this study is multiple regression, because in accordance with the purpose of this study is to analyze the effect of the independent variable on the dependent variable. The data in this study used purposive sampling method. The number of samples obtained as many as 9 companies with a total of 45 data. The object used is a banking company listed on the Indonesia Stock Exchange for 5 years from 2016-2020. The data was obtained by accessing the IDX's official website, namely www.idx.co.id. The analysis technique used is descriptive analysis, classical assumption test, multiple linear regression analysis, simultaneous test (F test), partial test (t test), coefficient of determination test (R2) using SPSS 26 tool. The results of this study indicate that the size of the board of commissioners and the size of the company affect financial performance, while the size of the board of directors has no effect on financial performance. Keywords: Financial Performance, Good Corporate Governance